Effective management of pulmonary embolism after initial diagnosis of acute coronary syndrome: a case report highlighting differential diagnosis challenges - Rao, Jiahuan; Wang, Zhiyan; Chen, Haibo (Frontiers in Medicine, 2025)
Pulmonary embolism (PE) often presents with symptoms similar to acute coronary syndrome (ACS), making diagnosis challenging. We report a case of a 55-year-old male with hypertension, chronic kidney disease, and hyperuricemia who developed chest pain and shortness of breath. Initial evaluation suggested ACS due to electrocardiogram changes and elevated cardiac biomarkers. However, coronary angiography (CAG) showed no significant stenosis, prompting further diagnostic workup. Computed tomography pulmonary angiography (CTPA) confirmed PE, likely secondary to deep vein thrombosis (DVT) in the right lower extremity. The patient was treated with an inferior vena cava (IVC) filter and thrombus aspiration, followed by anticoagulation therapy. This case highlights the critical need to differentiate PE from ACS and emphasizes the importance of a multidisciplinary approach in managing thromboembolic events to ensure optimal patient outcomes.